THE ROLE OF THE NOTARY IN SETTLEMENT OF CRIMINAL CASES BASED ON RESTORATIVE JUSTICE - Adisti, Neisa Angrum; Mardiansyah, Alfiyan; Nurillah, Isma; Banjarani, Desia Rakhma; Dedeng (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
Restorative Justice is an effort to find a peaceful process for resolving cases outside of court. This research uses normative legal research methods. The urgency of resolving criminal cases based on restorative justice is essentially the resolution of criminal cases by involving the perpetrator, victim, family of the perpetrator/victim, and other related parties to jointly seek a fair solution by emphasizing restoration to the original condition, and not retaliation. The main point of resolving criminal cases based on restorative justice is the existence of a peace agreement between the victim and the perpetrator of the crime. Peace agreement and fulfillment of the rights of victims of criminal acts. To prepare a peace agreement signed by the parties, of course it must be formulated in writing and can be drafted and signed in the presence of an authorized official. If necessary, this is where the role of a Notary can be used in drafting a peace agreement through a peace deed made and signed before a Notary. To strengthen the validity of the peace agreement letter and the need for legal protection, guarantees in fulfilling the rights of the victim, to avoid acts of default on the peace agreement between the criminal perpetrator and the victim, it can be formulated through an authentic deed, namely a peace deed made and signed before a Notary.